Shallot Peel Infusion Prevents Bronchus Epithelium Thickening And Cilia Shortening In Cigarette Smoke-Induced Wistar Rats - Bintang, Muhammad Farrel Ravidinata Masoga; Dewi, Rosita; Efendi, Erfan; Helianti, Dina; Rachmania, Sheilla (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Cigarette smoke exposure is the major risk of chronic obstructive pulmonary disease, the third cause of death worldwide. Inhaled smoke triggers oxidative stress resulting in airway epithelium thickening and cilia shortening. Shallot (Allium cepa L.) peel contains flavonoid which can neutralize oxidative stress. This study aims to determine correlation between shallot peel infusion (SPI), bronchus epithelium thickness, and cilia length in cigarette smoke-induced rats; and establish maximum effective dose of SPI. Rats were divided into normal; cigarette; SPI 125, 250, 500, 1,000, 2,000 mg/kgBW groups. Two hours after administration, rats were exposed to cigarette smoke 2 cigarettes/day for 28 days. Hematoxylin-eosin-stained bronchus was observed and variable measurements were carried out. Comparation tests of epithelium thickness and cilia length between normal and cigarette group showed significant difference (p<0.05); Pearson coefficient between SPI dose and epithelium thickening was -0.614, Spearman coefficient between SPI dose and cilia length was 0.860; and maximum effective dose to prevent bronchus epithelium thickening and cilia shortening are 1,275.4 mg/kgBW and 1,325.8 mg/kgBW. In conclusion, the higher the SPI dose, the lower epithelium thickness, the higher cilia length. Maximum effective dose of SPI to prevent bronchus epithelium thickening and cilia shortening are 1,275.4 mg/kgBW and 1,325.8 mg/kgBW.